God Values the Lives of My Out-Group More Than I Do: Evidence From Fiji and Israel. Issue 7 (September 2020) - Pasek, Michael H.; Shackleford, Crystal; Smith, Julia M.; Vishkin, Allon; Lehner, Anne; Ginges, Jeremy
Does God want people to favor coreligionists or to treat in-group and out-group members equally? To test people's beliefs about God's moral preferences, we conducted three preregistered studies. Study 1 was a field study with Christian and Muslim Fijians ( N = 188). Study 2 was an online study with Jewish Israelis ( N = 384). Study 3 was a field study with Christian and Hindu Fijians ( N = 539). Across studies, participants indicated whether an in-group member should sacrifice his life to save five in-group members (in one dilemma) or out-group members (in a second dilemma). For each dilemma, they then indicated what God would prefer. Participants believed that, compared with themselves, God would more strongly approve of an in-group member saving out-group members. Results generalize results from previous studies with Muslim Palestinians, providing cross-cultural evidence that religious believers think God prefers more universal moral reasoning than they do themselves.